ANALISIS UJI LAIK FUNGSI JALAN ASPEK TEKNIS PADA RUAS JALAN NASIONAL TAMBU â€“ TOMPE PROVINSI SULAWESI TENGAH - Andria Muharami Fitra (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2020)
Road safety is defined as physical fulfillment of road elements according to its technical requirements and roadside conditions so that the road does not contribute to traffic accidents. The condition of roads that meet technical requirements is also called roadworthiness. This paper aims to review safety aspects of road worthiness tests. The study was conducted using qualitative approach based on procedures for roadworthiness test according to Minister of Public Works Regulation No. 11/PRT/M/2010. Data from field test results and surveys are then processed to obtain roadworthiness categories by referring to six technical components, namely geometric, pavement structures, bridges, right of way, traffic management and road equipment. The Tambu-Tompe National Road section in Central Sulawesi was chosen as the case study. The results indicated that the segment is categorized as â€œConditionalâ€ where the proportion of â€œEligibleâ€ and â€œConditionalâ€ is 44% and 56%. The results of the study can be used by road authorities to determine priority of fulfillment of road function category. Keywords: roadworthiness, road safety analysis, road physical inspection, road technical requirements